A NEW MOUSE MODEL TO UNRAVEL THE MECHANISM OF SIRT1 ACTIVATION. (16th November 2018) - Amorim, J; Tackur, S; Bonkowski, M; Rolo, A; Palmeira, C; Sinclair, D
Abstract: SIRT1 is an NAD+-dependent deacetylase and one of the seven-member family of sirtuins that play a key role in the regulation of metabolism, DNA repair, inflammation, chromatin structure, and aging in mammals. Activation of SIRT1 improves mitochondrial function, treats hyperglycemia and fatty liver in mice and provides cardioprotection. The SIRT1 deacetylase reaction is one of the most complicated in the biological world, carrying out a two-step reversible reaction involving a covalently attached peptidyl intermediate. In collaboration with the de Cabo lab, we reported that STACs can increase the mean and maximum lifespan of mice by up to 22%. In humans, SRT2104, was able to alleviate psoriasis. Whether STACs such as resveratrol and SRT1720 mediate their health benefits via direct SIRT1 activation remains an unsolved question in the field, but one that will help guide drug development. SIRT1-activating compounds (STACs) work by binding to the N terminus of SIRT1 and lowering the Km for the substrate. Mutation of the mE222 residue adjacent to the STAC binding domain (SCD) prevents SIRT1 activation. We have generated a knock-in mouse model that is a homozygous mutant for E222K and are using it to precisely determine which of the biological effects if STACs such as resveratrol are due to SIRT1 activation. These studies will determine which diseases STACs could treats in humans and how they can be improved to increase their potency.